Biased-manager hiring in a market with network externalities and product compatibility - Shih-Hao Huang; Chien-Shu Tsai; Jen Yao Lee; Su-Ching Tsai (Games, 2025)
This paper studies biased-manager hiring in a market with network externalities and product compatibility. We show that the aggressivity of a biased manager has a non-linear relationship with product compatibility; however, since both owners want to hire aggressive managers, product compatibility is irrelevant to the type of manager the owner hires. In Cournot competition, product compatibility is crucial in alleviating the 'prisoner's dilemma' due to the net network effect of network externalities with product compatibility. In Bertrand competition, the 'prisoner's dilemma' is resolved when the augmented net network effect of product compatibility is large.
Keywords: D43; L13; L14; 330; network externalities; product compatibility; biased manager; Bertrand; Cournot